Iridium-Catalysed C–H Borylation Facilitates a Total Synthesis of the HRV 3C Protease Inhibitor (±)-Thysanone - Schünemann, Katrin; Furkert, Daniel P.; Connelly, Stephen; Fraser, John D.; Sperry, Jonathan; Brimble, Margaret A. (Synlett, 2014)
A new total synthesis of the HRV 3C protease inhibitor (±)-thysanone is described. The synthetic route hinges on an iridium-catalysed borylation to install the resorcinol-derived component of the natural product.
Keywords: thysanone; oxa-Pictet–Spengler reaction; pyranonaphthoquinone; HRV 3C protease; CH activation